The Influence of Learning Independence and Intelligence Quotient on Students’ Mathematical Creative Thinking Skills - Ervina Setianingrum; Kintoko Kintoko; Deny Hadi Siswanto (Riemann: Research of Mathematics and Mathematics Education, 2025)
This study aims to examine the influence of learning independence and Intelligence Quotient (IQ) on students’ mathematical creative thinking skills. The research employed a quantitative approach with an ex post facto design and was conducted at SMPN 5 Purworejo during the odd semester of the 2024/2025 academic year. The population comprised seventh-grade students, from whom 32 participants were selected through purposive sampling based on the availability of official IQ test results from a professional psychological institution. The research instruments included an essay test measuring creative thinking skills based on four indicators, namely fluency, flexibility, elaboration, and originality; a learning independence questionnaire covering six assessment aspects; and documentation of students’ IQ scores. Data analysis consisted of descriptive statistics, prerequisite testing, and multiple linear regression analysis using SPSS version 25. The results showed that learning independence and IQ significantly affected students’ mathematical creative thinking skills, both partially and simultaneously. Learning independence had a more dominant effect than IQ. Together, both variables explained 92.5% of the variance in students’ mathematical creative thinking skills.